Navigating Job Insecurity: The Role of Islamic Personality, Forgiveness, and Social Support on the Well-Being of ASN PPPK Lecturers - Iredho Fani Reza; Eko Oktapiya Hadinata; Kiki Cahaya Setiawan; Nasywa Syahira Oktaviani; Salsabila Nur Kamilah; Zarnalia Amanda (International Journal of Islamic Educational Psychology, 2025)
In the midst of structural transitions within Indonesia’s civil service system, ASN-PPPK Lecturers face unique psychological challenges, including contractual uncertainty, administrative pressure, and disparities in remuneration. These stressors threaten their subjective well-being (SWB), which is essential for professional performance and institutional resilience. This study aims to analyze the influence of gratitude, forgiveness, Islamic personality, and social support on the SWB of   ASN-PPPK Lecturers. Using a quantitative correlational design, the study involved 401 respondents selected through purposive sampling. Data were analyzed using multiple regression via JASP version 0.95.3.0. The results indicated that forgiveness, Islamic personality, and social support had a significant influence on SWB, while gratitude exhibited a positive but statistically insignificant effect. These findings implied that internalized Islamic values and interpersonal resources played a more critical role in sustaining lecturers’ well-being than individual emotional appreciation alone under structurally constrained conditions. Therefore, universities are encouraged to develop institutional policies that strengthen social support systems, foster forgiveness-based conflict management, and integrate Islamic personality development into lecturer mentoring and well-being programs. From the perspective of Islamic psychology, this study underscores the importance of contextualizing spiritual constructs within structural realities. It supports the advancement of integrative models of well-being that combine faith-based values with organizational interventions.